Breaking the Body of Evangelical Whiteness: A Womanist Ethic of Encounter for Faith-Based Anti-Trafficking Work - Nicole S. Symmonds (Religions, 2023)
For the last thirty years, white evangelical Christians have been one of the most prominent groups in the anti-trafficking movement in North America. Whether advocating for policy changes on behalf of survivors, interacting with populations vulnerable to sexual exploitation, or staging rescues, these moral actors use Christian religious practices and values to respond to trafficking and commercial sex work. Anti-trafficking work is coated with and coded by evangelical whiteness, which uses the norms of sexual, social, and racial purity in their interactions with and recovery of trafficking victims and survivors. In response to the white evangelical stronghold on anti-trafficking interventions, the womanist ethic of encounter utilizes womanist frameworks to center the historical realities lived experience of Black women and talk back to the history of evangelical whiteness in anti-trafficking work. Secondly, it focuses on how to interact with the holistic body of Black women in the urban mission field of anti-trafficking. Finally, the womanist ethic of encounter seeks to bridge the gap between the Protestant moralistic centering of the word of the Gospel that coats rescue and recovery efforts and asserts a Catholic centering of the Eucharist to clarify the power of sacrificing and breaking the body of whiteness in anti-trafficking work.